BLOCKCHAIN TECHNOLOGY IMPLEMENTATION ON MEDICAL RECORDS DATA MANAGEMENT: A REVIEW OF RECENT STUDIES - Dian Budi Santoso; Anis Fuad; Guntur Budi Herwanto; Ahmad Watsiq Maula (Poltekkes Kemenkes Semarang, 2020)
Blockchain first introduced and implemented in digital currency management and transactions. Its application to medical records data management is a novelty. This paper described the implementation of blockchain technology in the healthcare industry, especially in medical records data management A literature review was conducted on three popular databases, ScienceDirect, SpringerLink, and IEEE Xplore with the keywords